2010
DOI: 10.1021/ic100636j
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Interpretation of the 1H Photo-Chemically Induced Dynamic Nuclear Polarization Enhancements Characterizing Photoreduced Polyazaaromatic Ru(II) Coordination Complexes

Abstract: The unprotonated and protonated monoreduced forms of the polyazaaromatic Ru(II) coordination complexes [Ru(tap)(3)](2+) and [Ru(tap)(2)(phen)](2+) (tap = 1,4,5,8-tetraazaphenanthrene ; phen = 1,10-phenanthroline), that is, [Ru(tap)(3)](*+), [Ru(tap)(2)(phen)](*+), [Ru(tap)(2)(tap-H)](*2+), and [Ru(tap)(tap-H)(phen)](*2+), were studied by Density Functional Theory (DFT). The electron spin density of these radical cations, the isotropic Fermi-contact, and the anisotropic dipolar contributions to the hyperfine co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…26 An isotope effect is also observed when [Ru(TAP)2(dppz)] 2+ oxidizes 5′-GMP 12 and CIDNP studies with other [Ru(TAP)2L 2+ complexes suggest that this process might proceed by PCET within the solvent cage resulting in the formation of Ru(TAP)(TAPH)(dppz)] 2+ (equation 4). [13][14][15][16] [Ru(TAP)2(dppz)]…”
Section: Dft Calculations On the Electronic And Vibrational Absorptiomentioning
confidence: 99%
See 1 more Smart Citation
“…26 An isotope effect is also observed when [Ru(TAP)2(dppz)] 2+ oxidizes 5′-GMP 12 and CIDNP studies with other [Ru(TAP)2L 2+ complexes suggest that this process might proceed by PCET within the solvent cage resulting in the formation of Ru(TAP)(TAPH)(dppz)] 2+ (equation 4). [13][14][15][16] [Ru(TAP)2(dppz)]…”
Section: Dft Calculations On the Electronic And Vibrational Absorptiomentioning
confidence: 99%
“…More recently a series of detailed photo-CIDNP (chemically induced dynamic nuclear polarization) studies of the reduction of various [Ru(TAP)2(L)] 2+ with 5′-GMP and other reducing biomolecules have been reported by Kirsch-De Mesmaeker, Luhmer and coworkers. [13][14][15][16] With 5′-GMP as quencher, strongly enhanced absorption signals are found, predominantly for the 2,7-TAP protons (much weaker for the 3,6-TAP protons and absent for the 9,10-TAP protons) (see Figure 1 for the numbering of atoms in TAP), while a strong effect is also observed for the H8 of the GMP. This result is consistent with formation of the reduced metal complex and the oxidized nucleotide in the solvent cage; the CIDNP signal arises because of the competition between the back-electron transfer and the escape of the two radical species.…”
Section: Introductionmentioning
confidence: 99%
“…These calculations are based on the determination of the electronic structure of the mono-reduced form of Ru(II) complexes in gas phase and aqueous solution. Recently, some of us showed that the electron spin density and the isotropic Fermi contact contribution to the hyperfine interactions with the 1 H nuclei agree remarkably well with the observed 1 H photo-CIDNP enhancements [34]. Thus, combined photo-CIDNP experiments and DFT calculations open up new important perspectives for the study of polyazaaromatic Ru(II) complexes photoreactions.…”
Section: Dna Intercalating Complexesmentioning
confidence: 53%
“…Similar distances are expected in the complex [Ru(tap) 2 (hat)] 2+ ; the corresponding hat protons are indicated in italic. See Figs and for atom numbering …”
Section: Resultsmentioning
confidence: 99%
“…Calculated distances between the 1 H nuclei of the phen and tap ligands in the complex [Ru(tap) 2 (phen)] 2+ are quoted in Table 1. [4,5] The shortest interligand distances are found between 1 H in ortho position of a chelating N atom, i.e. between phen H-2,9 and tap H-6 (~3.3 Å), then between phen H-2,9 and tap H-3 (~3.5 Å; see also Supporting Information).…”
Section: Resultsmentioning
confidence: 99%